POLITIK ISLAMISASI KERAJAAN GOWA-TALLO TERHADAP TIGA KERAJAAN TELLUMPOCCOE (BONE, SOPPENG, WAJO) PADA ABAD XVII - Siswadi, Puji (Rihlah: Jurnal Sejarah dan Kebudayaan, 2016)
The results showed that the Kingdom of Gowa-Tallo in spreading Islam using two methods, namely, by way of peace and war. The way of peace carried out by the Kingdom of Gowa-Tallo in spreading Islam in South Sulawesi received good response among the Kingdom's around the Kingdom of Gowa-Tallo. But how different is the case with the third kingdom of Tellumpoccoe (Bone, Soppeng, and Wajo) are included in the Bugis kingdom. The third kingdom did not heed what the Sultan of Gowa's call to embrace Islam. For the rejection of the then Sultan of Gowa attacks on the third kingdom of the Bugis. With the Kingdom's attack was successfully converted to Islam. But one thing that should be known that the Sultan of Gowa offensive not because the Bugis third kingdom of rejecting Islam but his refusal way that does not comply with customs regulations. So Musu 'Asselengngeng said by Chritian Pelras needed reconsideration. Then the political hegemony of political Islamization Gowa-Tallo did not appear during the reign of Sultan Alauddin. But during the reign of Sultan Malikussaid and Sultan Hasanuddin hegemony comes as La Maddaremmeng applying Islamic rules that eliminate said system of slavery, then when the people and their nobles Bone kingdom was forced to help build the fortress Somba Opu